Initial investigations of a novel bioluminescence method for imaging dental demineralization. Issue 5 (28th January 2021) - Longbottom, Christopher; Vernon, Bruce; Perfect, Emma; Haughey, Anne‐Marie; Christie, Adam; Pitts, Nigel
Abstract: Objectives: In this in vitro study, a bioluminescent marker was investigated for its potential to illuminate the assessment of dental caries and dental erosion, which are significant clinical and public health problems, through its binding of those ions, notably Ca 2+, known to be released during the process of demineralization. Materials and Methods: The light output from the selected bioluminescent marker was investigated in several experiments, including: (a)contact with a range of Ca 2+ ion concentrations; (b) treatment of extracted teeth with solutions of differing pH, followed by application of the bioluminescence marker to assess Ca 2+ ion release; and (c) application of the marker to freshly extracted teeth with natural and artificially created caries lesions on occlusal and smooth surfaces to image the Ca 2+ ion distribution. Results: The results of: experiment (a) showed that the light output from the marker increases with increasing Ca 2+ concentration and of experiment (b) showed increases in light being observed as increasingly acidic solutions were applied. The results of experiment (c) showed the bioluminescence images of the extracted teeth produced "demineralization maps" of the imaged surfaces. Conclusions: These results demonstrate the ability of a novel bioluminescence technology to image Ca 2+ ions on tooth enamel surfaces which has potential in dental caries and dental erosion applications and provides the scientific basis for the ongoing development of that novel technology.